2021
DOI: 10.4103/idoj.idoj_881_20
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Dermal Macular Hyperpigmentation

Abstract: Acquired dermal macular hyperpigmentation (ADMH) is an umbrella term that includes disorders clinically characterized by small and large pigmented macules/patches and histopathologically showing an evidence of current or resolved interface dermatitis with pigment incontinence, without clinically significant prior inflammatory phase. The term intends to include diseases previously described in the literature as lichen planus pigmentosus, Riehl's melanosis/pigmented cosmetic dermatitis and ashy dermatosis/erythe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Moreover, some chemicals implicated in PCD not only stimulate melanogenesis but are also known photosensitizers. 13 In our study, we explored sunscreen use in both the patient and control groups, but we found no significant difference in sunscreen use between the two groups. A more detailed history, including daily use patterns, such as amount of sunscreen agent and duration of wearing, is necessary to achieve meaningful results.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Moreover, some chemicals implicated in PCD not only stimulate melanogenesis but are also known photosensitizers. 13 In our study, we explored sunscreen use in both the patient and control groups, but we found no significant difference in sunscreen use between the two groups. A more detailed history, including daily use patterns, such as amount of sunscreen agent and duration of wearing, is necessary to achieve meaningful results.…”
Section: Discussionmentioning
confidence: 85%
“…It is proposed that repetitive or persistent contact with low-level allergens induces cytolytic reactions, which is characterized by disruption of the basement membrane and pigment incontinence rather than frank eczematous reactions. 11,13,15 Even if subtle eczema develops, individuals with darker skin have difficulty noticing erythema or pigmentation, especially if there are no symptoms such as itching. Moreover, people often ignore mild symptoms and continue to use hair dyes for cosmetic reasons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…What is noteworthy is that in an open-label pilot study, oral mycophenolate mofetil was initially applied in acquired dermal macular hyperpigmentation (ADMH), an umbrella term including RM. 19 , 20 Mycophenolate mofetil is one of immunomodulators, which can reduce immunosuppressive effect. It can reduce the hyperpigmentation through targeting the lymphocytes’ de-novo purine production pathway and probably inhibiting fibroblasts, which are also recognized with melanin contained.…”
Section: Drug Therapymentioning
confidence: 99%